Satisfaction and stability within long-term relationships involving trait hostility - Harrison, Joy (My University, 2001)
This study examined correlates of trait hostility within long-term relationships. In accordance with the rules of complementarity put forth by interpersonal theorists, it was predicted that hostile individuals would more often be paired with similarly hostile individuals, and that, counter-intuitively, such relationships would involve high levels of satisfaction and stability. The participants were 70 couples involved in long-term romantic relationships. Both partners of each couple completed an anonymous, 20-minute questionnaire that included measures of personality, relationship satisfaction, and relationship commitment The results indicate that the existence of complementarity and its association widi relationship satisfaction and stability are different for friendliness and hostility, and depend upon whose ratings of personality are compared. When participants’ Friendliness-Hostility self-ratings were compared to their ratings of their partners’ Friendliness-Hostility, complementarity was only evident among friendly participants, but not hostile participants. Further, both friendly and hostile participants reported greater relationship satisfaction and commitment when they rated their partners as friendly, rather than hostile. When partners’ Friendliness- Hostility self-ratings were compared, the results were inconsistent and varied by gender. The patterns of results are discussed in relation to interpersonal theory, base-rate hypotheses, and theories of social influence.
Keywords: Interpersonal relations research; Couples psychological testing; Hostility (Psychology)